Optical adhesive sheet

By introducing components such as acrylic copolymers and oligomers into the optical glue, the problem of the optical glue being prone to bubbles and layering on the plastic panel is solved, and good adhesion and weather resistance are achieved in high temperature and high humidity environments. It is suitable for touch display modules made of plastic materials.

CN120464335AActive Publication Date: 2025-08-12CROWN TAICANG ADHESIVE PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510969775.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-08-12
Estimated Expiration
2045-07-15

AI Technical Summary

Technical Problem

Existing optical glues are prone to bubbles and delamination on plastic panels, and cannot maintain good adhesion in high temperature and high humidity environments.

Method used

The acrylic copolymer is used, which contains 10 to 20 wt% hydrophilic monomer, and combines the acrylic oligomer, crosslinked monomer and silane coupling agent to form an optical adhesive sheet with good flexibility and bonding properties.

Benefits of technology

Effectively prevent air bubbles from escaping, improve the foaming and weather resistance of the adhesive sheet, enhance the bonding reliability, and is suitable for touch display modules made of plastic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120464335A_ABST
    Figure CN120464335A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optical adhesives, in particular to an optical adhesive sheet. The optical adhesive sheet comprises an acrylic copolymer, and the total weight of monomer components in the acrylic copolymer is 100 wt%, and the hydrophilic monomer accounts for 10-20 wt%; wherein the structure of the hydrophilic monomer is as follows: # imgabs0 #, and n is a natural number between 1 and 15. The optical bonding sheet is suitable for bonding of a plastic touch display module, has good foaming resistance, and also has good bonding performance and weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical adhesives, and in particular to an optical adhesive sheet. Background Art

[0002] Optical Clear Adhesive (OCA), with its excellent optical and bonding properties, has become a key bonding material for touchscreen display components and is widely used in products with touchscreen displays, such as mobile phones, tablets, and automotive displays. Due to the diverse application environments of touchscreen display modules, optical adhesives must maintain optical clarity and bonding stability while also exhibiting excellent weather resistance, such as heat and humidity resistance.

[0003] With the rapid development of polymer materials, such as polymethyl methacrylate (PMMA), polycarbonate (PC), cyclic olefin copolymer (COC), and cyclic olefin polymer (COP), plastic panels are becoming lightweight, highly secure, and low-cost. These panels are gradually replacing traditional glass substrates and are widely used in automotive displays. However, due to the long-term exposure of automotive displays to high temperature and high humidity outdoors, the polymer materials within the plastic panels generate gases due to the heat and humidity. If these gases are not discharged in a timely manner, they will affect the adhesion of optical adhesives to the plastic panels.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] The present invention provides an optical adhesive sheet. The optical adhesive sheet provided by the present invention has good foaming resistance and moisture and heat resistance, can avoid the generation of bubbles when bonding with a plastic panel, and improves bonding reliability.

[0006] In order to achieve the above-mentioned object of the present invention, the present invention provides an optical adhesive sheet, comprising an acrylic copolymer, wherein the acrylic copolymer contains 10 to 20 wt % of a hydrophilic monomer, based on 100 wt % of the total weight of monomer components in the acrylic copolymer; Wherein, the structure of the hydrophilic monomer is as follows: , where n is a natural number between 1 and 15.

[0007] Furthermore, the acrylic copolymer has a weight average molecular weight Mw of 1,000,000 to 5,000,000 g / mol.

[0008] Furthermore, the optical adhesive sheet further includes an acrylic oligomer, and the content of the acrylic oligomer is 5 to 15 parts by weight relative to 100 parts by weight of the acrylic copolymer.

[0009] Furthermore, the weight average molecular weight Mw of the acrylic oligomer is 20,000-100,000 g / mol.

[0010] Furthermore, based on 100 wt % of the total weight of monomer components in the acrylic oligomer, the acrylic oligomer contains 85-95 wt % of the high Tg monomer.

[0011] Furthermore, the high Tg monomer includes at least one of linear and / or branched alkyl (meth)acrylates, alicyclic (meth)acrylates and aromatic (meth)acrylates.

[0012] Furthermore, the high Tg monomer is selected from alicyclic (meth)acrylates.

[0013] Furthermore, the optical adhesive sheet further includes a cross-linking monomer, and the content of the cross-linking monomer is 0.1 to 0.5 parts by weight relative to 100 parts by weight of the acrylic copolymer.

[0014] Furthermore, the cross-linking monomer is a (meth)acrylate monomer with a functionality of 2 to 6.

[0015] Furthermore, the optical adhesive sheet further comprises a silane coupling agent, and the content of the silane coupling agent is 0.1 to 1 part by weight relative to 100 parts by weight of the acrylic copolymer.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The optical adhesive sheet of the present invention introduces a certain amount of hydrophilic monomer into the acrylic copolymer. On the one hand, the affinity of the hydrophilic chain segment with gas is utilized to promote the dissolution of bubbles and prevent the escape of bubbles. On the other hand, the hydrophilic chain segment in the hydrophilic monomer structure has good wettability, which can effectively enhance the initial adhesion of the optical adhesive sheet and improve the bonding performance. In addition, the hydrophilic monomer of this structure has good flexibility, which can enhance the deformation ability of the adhesive sheet.

[0017] (2) The optical adhesive sheet of the present invention is suitable for bonding touch display components, especially for bonding plastic materials. It not only has good blister resistance, but also has good wettability and weather resistance. DETAILED DESCRIPTION

[0018] The technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. However, those skilled in the art will understand that the embodiments described below are part of the embodiments of the present invention, not all of them, and are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or those recommended by the manufacturer. All reagents or instruments used, if the manufacturer is not specified, are commercially available conventional products.

[0020] In the description of the present invention, the term "(meth)acrylate" refers to any of methacrylate, acrylate, and a combination of methacrylate and acrylate, and other terms containing such definitions have the same meaning.

[0021] In the description of the present invention, the term "Tg" refers to "glass transition temperature".

[0022] Due to the different expansion coefficients between the plastic panel and the optical adhesive, and the plastic material's tendency to generate gas under high temperature and humidity, these factors affect the adhesion of the optical adhesive to the plastic panel, making it prone to bubbles, peeling, and delamination. Prior art (CN103242748A) attempts to prevent gas escape by increasing the rigidity of the optical adhesive. However, the inventors of this invention have discovered that increasing the rigidity of the optical adhesive reduces its wettability, thereby deteriorating the bonding performance. Furthermore, increased rigidity reduces deformation. When the expansion coefficients of the optical adhesive and the adhered object differ significantly, a certain gap inevitably forms, leading to delamination and peeling of the adhesive sheet.

[0023] Based on this, the present invention provides an optical adhesive sheet, comprising an acrylic copolymer, wherein the acrylic copolymer contains 10 to 20 wt% of a hydrophilic monomer, based on 100 wt% of the total weight of monomer components in the acrylic copolymer. The structure of the hydrophilic monomer is as follows:

[0024] Wherein, n is a natural number between 1 and 15, and can be 1, 5, 7, 8, 12, 15, or any natural number between the two values.

[0025] The inventors of the present invention have discovered that the hydrophilic segments in the hydrophilic monomer having the above molecular structure have good affinity with gas, which can promote the dissolution of bubbles and prevent the escape of bubbles. On the other hand, the hydrophilic monomer has good flexibility, which can improve the initial adhesion of the adhesive sheet and enhance the deformation ability of the adhesive to avoid peeling and delamination.

[0026] As the hydrophilic monomer of the above structure, a substance having the above structure can be synthesized by oneself, or a commercial product can be used. The commercial product substance is called methoxy polyethylene glycol acrylate, and examples thereof include MPE400A and MPE550A produced by Osaka Organic Chemical Industry Co., Ltd. of Japan.

[0027] In one specific embodiment, the acrylic copolymer comprises 10 to 20 wt% of a hydrophilic monomer, based on 100 wt% of the total weight of the monomer components. Specifically, the hydrophilic monomer content may be 10 wt%, 15 wt%, 20 wt%, or any value in between. Excessive hydrophilic monomer content is not recommended, as it can lead to polymerization failure and the inability to produce the desired polymer. However, too low a content can result in poor bubble reduction.

[0028] In a specific embodiment, the acrylic copolymer further contains a soft monomer, which is an alkyl (meth)acrylate having an alkyl group with 4 to 14 carbon atoms, including but not limited to at least one of 2-ethylhexyl acrylate (2-EHA), n-butyl acrylate (BA), dodecyl acrylate (LA) and isodecyl acrylate (IDA).

[0029] In one embodiment, the soft monomer content is not less than 50 wt % and not more than 60 wt % based on 100 wt % of the total weight of the monomer components in the acrylic copolymer. Limiting the soft monomer content to this range can improve the adhesive strength of the adhesive sheet.

[0030] In one embodiment, the acrylic copolymer further comprises a polar monomer, which effectively enhances the adhesive strength of the adhesive sheet. Polar monomers are monomers containing polar groups, such as carboxyl, hydroxyl, vinyl, or nitrogen-containing amide and amino groups. In the present invention, a combination of a polar monomer containing a hydroxyl group and a polar monomer containing a nitrogen atom is preferred.

[0031] The polar monomer containing a hydroxyl group is preferably a (meth)acrylate monomer containing a hydroxyl group, such as 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate, hydroxypropyl acrylate (HPA), and 4-hydroxybutyl acrylate (4-HBA). The hydroxyl-containing monomer may be selected alone or in combination of two or more.

[0032] In a specific embodiment, based on 100 wt % of the total weight of the monomer components in the acrylic copolymer, the content of the polar monomer containing a hydroxyl group is not less than 15 wt % and not more than 20 wt %.

[0033] In a specific embodiment, the polar monomer containing nitrogen atoms includes at least one of N-vinyl-2-pyrrolidone (NVP), N-vinylcaprolactam (NVC) and N,N-dimethylacrylamide.

[0034] In a specific embodiment, based on 100 wt % of the total weight of the monomer components in the acrylic copolymer, the content of the polar monomer containing nitrogen atoms is not less than 10 wt % and not more than 15 wt %.

[0035] In one embodiment, the weight average molecular weight of the copolymer obtained by polymerizing the monomers constituting the acrylic copolymer can be any suitable value, and in the present invention, it is preferably 1,000,000 to 5,000,000 g / mol, and more preferably 1,500,000 to 3,000,000 g / mol.

[0036] The acrylic copolymer can be prepared by conventional polymerization methods, such as free radical polymerization. In one embodiment, the preparation of the acrylic copolymer comprises: mixing the monomer components, adding a certain amount of photoinitiator, and initiating polymerization under ultraviolet light in a protective atmosphere. The acrylic copolymer can be obtained after the reaction is completed.

[0037] Furthermore, based on 100 parts by weight of the total amount of monomer components of the acrylic copolymer, the amount of the photoinitiator is 0.01 to 0.1 parts by weight.

[0038] Furthermore, the photoinitiator is not particularly limited, and conventional initiators can be selected as long as they can initiate polymerization, such as at least one of fluoroboryl acrylate (photoinitiator 184), benzoin diethyl ether (photoinitiator 651) and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO).

[0039] Furthermore, the protective gas may be at least one of nitrogen and argon.

[0040] In a specific embodiment, the optical adhesive sheet further includes an acrylic oligomer, and the content of the acrylic oligomer is 5 to 15 parts by weight relative to 100 parts by weight of the acrylic copolymer, specifically 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 15 parts by weight or any value between any two ends thereof; regulating the amount of acrylic oligomer in the adhesive within the above range is beneficial to maintaining a good balance between the initial adhesion, high temperature resistance and weather resistance of the adhesive.

[0041] In one specific embodiment, the acrylic oligomer contains 85-95 wt% of a high-Tg monomer, based on 100 wt% of the total weight of the monomer components in the acrylic oligomer. For example, the content can be 85 wt%, 88 wt%, 90 wt%, 92 wt%, 95 wt%, or any value between these two values. The present invention stipulates that the acrylic oligomer contains a relatively high content of high-Tg monomer to ensure that the acrylic oligomer has a higher Tg, impart a certain degree of rigidity to the adhesive, improve the storage modulus at high temperatures, and enhance weather resistance in hot and humid environments. The high-Tg monomer described in the present invention refers to a monomer having a Tg value greater than 10°C, preferably greater than 50°C, and more preferably greater than 100°C.

[0042] In a specific embodiment, the high Tg monomer includes at least one of linear and / or branched alkyl (meth)acrylate, alicyclic (meth)acrylate and aromatic (meth)acrylate, preferably alicyclic (meth)acrylate.

[0043] In one specific embodiment, the alicyclic (meth)acrylates include isobornyl methacrylate (IBOMA), biscyclopentenyl methacrylate (DCPMA), biscyclopentenylethoxy methacrylate, dicyclopentyl methacrylate, 1-adamantyl methacrylate (ADMA), 2-methyl-2-adamantyl methacrylate, and 2-ethyl-2-adamantyl methacrylate. The high Tg monomer may be at least one of the above monomers.

[0044] In a specific embodiment, the aromatic (meth)acrylate includes at least one of aryl (meth)acrylate, phenoxyalkyl (meth)acrylate, and aryl alkyl (meth)acrylate.

[0045] Furthermore, the aryl (meth)acrylate may include phenyl (meth)acrylate; the phenoxyalkyl (meth)acrylate includes 2-phenoxyethyl (meth)acrylate; and the aryl alkyl (meth)acrylate includes benzyl (meth)acrylate.

[0046] In one embodiment, the acrylic oligomer further contains a polar monomer, which can be any of the polar monomers listed above for the acrylic copolymer. The polar monomer in the acrylic oligomer can be the same as or different from the polar monomer selected for the acrylic copolymer.

[0047] In a specific embodiment of the present invention, based on 100 wt% of the total weight of the monomer components in the acrylic oligomer, the polar monomer is contained in an amount of 5 to 15 wt%, for example, 5 wt%, 8 wt%, 10 wt%, 12 wt%, 15 wt% or any value in between.

[0048] In one specific embodiment, the weight-average molecular weight (Mw) of the acrylic oligomer is 20,000 to 100,000 g / mol, for example, 20,000 g / mol, 40,000 g / mol, 50,000 g / mol, 60,000 g / mol, 80,000 g / mol, 100,000 g / mol, or any value therebetween. Limiting the weight-average molecular weight of the acrylic oligomer to this range can yield an adhesive with well-balanced tack, toughness, and weather resistance.

[0049] In one specific embodiment, a chain transfer agent may be added to the acrylic oligomer during polymerization to control the weight-average molecular weight of the oligomer. Conventional chain transfer agents can be selected, such as thiols, such as n-dodecyl mercaptan, 2-mercaptoethanol, pentaerythritol tetrakis(3-mercaptobutyrate) (PE1), or the commercially available 2,4-diphenyl-4-methyl-1-pentene (TPMS). The amount of the chain transfer agent used is 0.3 to 3 parts by weight, based on 100 parts by weight of the total monomer components in the acrylic oligomer.

[0050] In a specific embodiment of the present invention, the acrylic oligomer can be polymerized in a conventional manner. For example, its preparation includes: weighing the monomer components, chain transfer agent and solvent in proportion, mixing them evenly under a protective atmosphere, then adding a certain amount of thermal initiator, heating to a certain temperature to carry out polymerization reaction, and removing the solvent after the reaction is completed to obtain the acrylic oligomer.

[0051] Furthermore, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0052] Furthermore, the polymerization reaction temperature is 70-80°C, and the reaction time is 2-6 hours. The specific reaction temperature and time can be adjusted according to the type of initiator, so as to be able to initiate polymerization.

[0053] Furthermore, the thermal initiator can be a conventional azo initiator or an organic peroxide initiator. Azo initiators include, but are not limited to, azobisisobutyronitrile (AIBN) and azobisisoheptanenitrile. Organic peroxide initiators include, but are not limited to, dibenzoyl peroxide (BPO) and lauroyl peroxide. The thermal initiator can be selected from at least one of the aforementioned substances. The amount of the thermal initiator used is 0.1 to 2 parts by weight, based on 100 parts by weight of the total monomer components in the acrylic oligomer.

[0054] Furthermore, the solvent may be a conventional organic solvent, including but not limited to at least one of ethyl acetate (EA), toluene (Tol), and methyl vinyl ketone (MEK). The amount of the solvent used is 50 to 200 parts by weight based on 100 parts by weight of the total weight of the monomer components in the acrylic oligomer.

[0055] In one embodiment, the optical adhesive sheet further includes a crosslinking monomer capable of crosslinking and polymerizing the acrylic copolymer. The crosslinking monomer can be a multifunctional (meth)acrylate monomer, preferably a (meth)acrylate monomer with a functionality of 2 to 6, such as 1,6-hexanediol diacrylate (HDDA) with a functionality of 2, ethoxylated trimethylolpropane triacrylate with a functionality of 3, and trimethylolpropane triacrylate (TMPTA) with a functionality of 3. At least one of these can be used as the crosslinking monomer.

[0056] The crosslinking monomer is present in an amount of 0.1 to 0.5 parts by weight relative to 100 parts by weight of the acrylic copolymer, specifically 0.1, 0.2, 0.3, 0.4, 0.5, or any value therebetween. The inclusion of an appropriate amount of crosslinking monomer increases the crosslink density of the cured system, thereby improving rigidity, maintaining a high modulus at high temperatures, and inhibiting bubble release.

[0057] In one specific embodiment, the optical adhesive sheet further includes a silane coupling agent. The content of the silane coupling agent is 0.1 to 1 part by weight relative to 100 parts by weight of the acrylic copolymer, specifically 0.1, 0.3, 0.5, 0.8, 1, or any value in between. The inclusion of an appropriate amount of the silane coupling agent can improve the adhesive's bond strength and resistance to wet-heat aging, and increase the adhesive sheet's affinity for the glass substrate.

[0058] In a specific embodiment of the present invention, the silane coupling agent includes at least one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane. The silane coupling agent in the present invention can also be a commercially available product, such as KBM-403 produced by Shin-Etsu Chemical Co., Ltd. of Japan.

[0059] In the present invention, there is no limitation on the preparation method of the adhesive, and commonly used preparation methods of adhesives can be used. The present invention provides a preparation method of an adhesive, comprising the following steps: mixing the components in proportion, stirring evenly, and then standing to defoam, thereby obtaining an adhesive to be coated.

[0060] It is understood that, for ease of production, transportation, and sales, the optically clear adhesive of the present invention is limited only to the composition of the components, not their form. That is, the components may be mixed or stored separately. The choice of mixed or separate storage can be determined based on actual use.

[0061] In a specific embodiment of the present invention, the thickness of the adhesive sheet can be set to different thicknesses according to specific needs, for example, it can be 100-200 μm, specifically 100 μm, 120 μm, 150 μm, 180 μm, 200 μm or any value between the two ends.

[0062] The present invention also provides an optional method for preparing the aforementioned adhesive sheet, comprising the steps of applying an adhesive to a release film, UV curing, and drying to obtain an adhesive sheet product. To facilitate roll packaging and transportation, the adhesive sheet may be further coated with a release film.

[0063] The coating method is not limited, and conventional coating methods such as roller coating, blade coating, or dip coating can be used. The thickness of the release film can be freely selected according to actual needs and is not particularly limited. For example, it can be set to 25 to 100 μm, and specifically can be 25 μm, 30 μm, 40 μm, 50 μm, 80 μm, 100 μm, or any value in between.

[0064] In a specific embodiment of the present invention, the UV curing intensity is 3 to 10 mW / cm 2 , irradiate for 1 to 5 minutes.

[0065] In a specific embodiment of the present invention, the drying temperature is 90-110° C., and the drying time is 2-5 minutes.

[0066] When the adhesive sheet product of the present invention is actually used, the release film is removed and the adhesive sheet is pasted between two adhered components.

[0067] The following specific examples are given to further illustrate the objects and advantages of the present invention, but these examples should not be considered as limiting the present invention. In the following examples, 1 g represents 1 part by weight.

[0068] Preparation Example A Preparation of acrylic copolymers In an open reactor, a certain amount by weight of a soft monomer, a hydrophilic monomer, a polar monomer and a photoinitiator are added, stirred and nitrogen is passed through, and then polymerization is carried out under ultraviolet light irradiation until the viscosity of the reactants reaches a specified range, thereby obtaining an acrylic copolymer A.

[0069] The preparation methods of the different acrylic copolymers in Preparation Example A are the same, except that the amounts or types of the components are different, as shown in Table 1 below.

[0070] Table 1 Raw material composition of acrylic copolymer

[0071] Note: In the above copolymer A6, the copolymerization failed due to the excessively high content of the hydrophilic monomer, and no effective copolymer could be formed.

[0072] The weight average molecular weight was determined by gel permeation chromatography (GPC) under the following conditions: 1) Chromatographic column: PLgel 10 μm MIXED-B (Part No: PL1110-6100), Pore Type: MIXED-B, Length / ID: 300×7.5 mm.

[0073] 2) Mobile phase: Tetrahydrofuran (THF) solution containing 2,6-di-tert-butyl-4-methylphenol as stabilizer, flow rate 0.5 mL / min.

[0074] 3) Injection concentration: 5.0 mg / mL, injection volume: 20 μL, column temperature: 40°C, detector temperature: 40°C.

[0075] 4) Standard sample: polystyrene (Easivial).

[0076] 5) Sample Preparation: Dissolve the sample in THF to a concentration of 5-10 mg / mL. Shake for 2 hours and let stand overnight. Aspirate the supernatant using a 2 mL disposable syringe. Filter the filtrate through a 0.45 μm filter into a dedicated sample vial. Prepare a THF blank and ensure the vial cap is securely sealed.

[0077] The GPC equipment used in the present invention is Agilent 1260 infinity II, and the weight average molecular weight test operation is performed according to the equipment instruction manual.

[0078] Preparation Example Group B Preparation of acrylic oligomers A certain amount of high-Tg monomer, polar monomer, chain transfer agent, and solvent were placed in a four-necked flask and stirred at 70°C under a nitrogen atmosphere. A certain amount of thermal initiator was then added, and the reaction was allowed to proceed at 70°C for 2 hours and then at 80°C for another 2 hours. After the reaction, the solvent, chain transfer agent, and unreacted monomer were dried at 130°C to obtain a solid acrylic oligomer B.

[0079] The preparation methods of different acrylic oligomers in Preparation Example Group B are the same, except that the amounts or types of the components are different, as shown in Table 2 below.

[0080] Table 2 Raw material composition of acrylic oligomers

[0081] Example 1 This embodiment provides an optical adhesive sheet, comprising the following components: 100 g of acrylic copolymer A1, 10 g of acrylic oligomer B1, 0.25 g of 1,6-hexanediol diacrylate (HDDA), and 0.5 g of silane coupling agent KBM-403.

[0082] The preparation method is as follows: the above materials are mixed evenly to obtain an adhesive, and the adhesive is coated on the surface of a 50 μm thick PET release film by a double roller at a power of 5 mW / cm 2 The film was irradiated with ultraviolet radiation intensity of 500 nm for 5 min and then baked at 100 °C for 3 min to obtain an adhesive sheet with a thickness of 150 μm.

[0083] Example 2 This example was carried out with reference to Example 1, with the only difference being the amounts of some components of the adhesive sheet. The rest were the same as Example 1. The specific differences are as follows: 5 g of acrylic oligomer B1, 0.5 g of HDDA and 0.1 g of silane coupling agent KBM-403.

[0084] Example 3 This example was carried out with reference to Example 1, with the only difference being the amounts and types of some components of the adhesive sheet. The rest were the same as Example 1. The specific differences are as follows: 15 g of acrylic oligomer B1, 0.1 g of trimethylolpropane triacrylate (TMPTA), and 1 g of silane coupling agent KBM-403.

[0085] Example 4 Group This example group was prepared with reference to Example 1, with the only difference being that the same amount of different acrylic copolymers prepared in Preparation Example A were used. The rest were the same as in Example 1. The specific differences are as follows: Example 4a: The acrylic copolymer is A2 prepared in Preparation Example A; Example 4b: The acrylic copolymer is A3 prepared in Preparation Example A; Example 4c: The acrylic copolymer is A4 prepared in Preparation Example A; Example 4d: The acrylic copolymer is A5 prepared in Preparation Example A.

[0086] Example 5 group This example group was prepared with reference to Example 1, with the only difference being that the same amount of different acrylic oligomers prepared in Preparation Example B were used. The rest were the same as in Example 1. The specific differences are as follows: Example 5a: The acrylic oligomer is B2 prepared in Preparation Example Group B; Example 5b: The acrylic oligomer is B3 prepared in Preparation Example B; Example 5c: The acrylic oligomer is B4 prepared in Preparation Example Group B; Example 5d: The acrylic oligomer is B5 prepared in Preparation Example B.

[0087] Comparative Example 1 This comparative example group was carried out with reference to Example 1, except that the amount of acrylic acid oligomer was different. The rest was the same as Example 1. The specific differences are as follows: Comparative Example 1a: 2.5 g of acrylic oligomer B1; Comparative Example 1b: 20 g of acrylic oligomer B1.

[0088] Test Case The optical adhesive sheets prepared in the above examples and comparative examples were subjected to the following tests. The test results are shown in Table 3.

[0089] (1) 180° peel strength test: The test was conducted in accordance with the international standard ASTM D3330 "Standard for Testing the Peel Strength of Pressure-Sensitive Tapes". The test panel was a PC board and the test specimen size was 300 mm × 24 mm. Room temperature peel strength test: After laminating the specimen to the PC board, place it at 23±1℃ and 50±5%RH for 20 minutes. The average adhesion force required to tear the specimen off the panel is measured, expressed in gf / 24 mm. 85°C peel strength test: After laminating the specimen to the PC board, place it at 23±1°C and 50±5% RH for 20 minutes. After placing it in an 85°C oven for 30 minutes, the average adhesion force required to tear the specimen off the panel is measured, expressed in gf / 24 mm.

[0090] (2) Initial adhesion test: Test according to the international standard ASTM D3121-17 "Standard Test Method for Bonding Pressure-Sensitive Adhesives by Rolling Balls" and record the corresponding steel ball number (#). The larger the ball number, the higher the initial adhesion.

[0091] (3) Bonding effect test: Cut the adhesive sheet for bonding PC board into 5 cm × 10 cm pieces. Use a vacuum bonding machine to bond the adhesive sheet and the opposite surface of PC board to the plain glass surface. Place the adhesive sheet at 0.5 MPa and 30°C for 30 min. Take it out and let it stand for 24 h. Visually observe the appearance of the adhesive sheet. If there is no bubble, whitening, delamination or other poor appearance, record it as OK. Otherwise, record the corresponding poor appearance phenomenon.

[0092] (4) High temperature and high humidity resistance test: The sample in (3) was placed at 0.5 MPa and 30°C for 30 min and then taken out and left to stand for 24 h. Then, it was placed at 85°C / 85%RH for 1,000 h. After taking it out, the surface of the adhesive sheet was visually inspected to see if there were any bubbles, whitening, delamination or other appearance defects. If not, the high temperature and high humidity resistance was recorded as OK. Otherwise, the corresponding appearance defects were recorded.

[0093] Table 3 Performance test results of different embodiments and comparative examples

[0094] The above test results show that the use of the hydrophilic monomer with the structure defined in the present invention as a comonomer of the acrylic copolymer can effectively improve the blister resistance of the adhesive sheet, and can also balance the initial tack, adhesion performance and peel strength of the adhesive sheet, which is conducive to avoiding delamination; and adding a certain amount of acrylic oligomer prepared with a high Tg monomer to the adhesive sheet helps to increase the rigidity and thus enhance the high temperature resistance of the adhesive sheet.

[0095] The test results of Example 4 indicate that the adhesive sheet prepared using the acrylic copolymer with the defined component composition and molecular weight range of the present invention can effectively improve the blister resistance of the adhesive sheet while also balancing the initial tack, adhesion performance, and peel strength of the adhesive sheet. However, if the hydrophilic monomer content is below the defined range, the improvement in blister resistance is poor. This is because the adhesive sheet is not hydrophilic enough and has insufficient affinity for bubbles released by PC, which prevents effective gas dissolution and leads to gas escape. When the hydrophilic monomer content is too high, its steric hindrance is relatively large, the copolymerization reaction activity is very low, and an effective polymer cannot be formed.

[0096] The test results of Example 5 show that by adding an acrylic oligomer within the molecular weight and content range specified in the present invention to an adhesive sheet, an adhesive sheet with balanced initial adhesion, high temperature resistance, and peel strength can be obtained. When the molecular weight of the acrylic oligomer is too high, the compatibility between the acrylic oligomer and the acrylic copolymer deteriorates, resulting in a white appearance. When the molecular weight of the acrylic oligomer is too low, it is difficult to ensure the modulus of the adhesive at high temperature, resulting in a decrease in high temperature and high humidity resistance.

[0097] The test results of Comparative Example 1 show that when the amount of acrylic oligomer used is too low, the high-temperature adhesion of the adhesive cannot be guaranteed, and the high-temperature and high-humidity resistance decreases; when the amount of acrylic oligomer used is too high, the initial adhesion of the adhesive sheet is poor, the bonding performance deteriorates, and delamination is prone to occur under high temperature and high humidity.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An optical adhesive sheet, characterized in that The optical adhesive sheet comprises an acrylic copolymer, and based on 100 wt % of the total weight of monomer components in the acrylic copolymer, contains 10 to 20 wt % of a hydrophilic monomer; Wherein, the structure of the hydrophilic monomer is as follows: , where n is a natural number between 1 and 15.

2. The optical adhesive sheet according to claim 1, wherein The acrylic copolymer has a weight average molecular weight (Mw) of 1,000,000 to 5,000,000 g / mol.

3. The optical adhesive sheet according to claim 1 or 2, wherein The optical adhesive sheet further includes an acrylic oligomer, wherein the content of the acrylic oligomer is 5 to 15 parts by weight relative to 100 parts by weight of the acrylic copolymer.

4. The optical adhesive sheet according to claim 3, wherein The weight average molecular weight Mw of the acrylic oligomer is 20,000 to 100,000 g / mol.

5. The optical adhesive sheet according to claim 4, wherein Based on 100 wt% of the total weight of the monomer components in the acrylic oligomer, 85-95 wt% of the high Tg monomer is contained.

6. The optical adhesive sheet according to claim 5, wherein The high Tg monomer includes at least one of linear and / or branched alkyl (meth)acrylates, alicyclic (meth)acrylates and aromatic (meth)acrylates.

7. The optical adhesive sheet according to claim 6, wherein The high Tg monomer is selected from alicyclic (meth)acrylates.

8. The optical adhesive sheet according to claim 3, wherein The optical adhesive sheet further includes a cross-linking monomer, and the content of the cross-linking monomer is 0.1 to 0.5 parts by weight relative to 100 parts by weight of the acrylic copolymer.

9. The optical adhesive sheet according to claim 8, wherein The cross-linking monomer is a (meth)acrylate monomer with a functionality of 2 to 6.

10. The optical adhesive sheet according to claim 8, wherein The optical adhesive sheet further includes a silane coupling agent, and the content of the silane coupling agent is 0.1 to 1 parts by weight relative to 100 parts by weight of the acrylic copolymer.

Citation Information

Patent Citations

  • Adhesive composition, adhesive layer, adhesive sheet and optical thin film

    CN103571405A

  • OPTICAL ADHESIVE COMPOSITION AND ADHESIVE FILM and ADHESIVE SHEET USING THE SAME

    CN111849361A

  • Adhesive and optical component protective sheet

    CN112375515A

  • Adhesive composition, adhesive layer, optical film with adhesive layer, and display device

    CN117683490A

  • Acrylic pressure-sensitive adhesive for foldable display screen and adhesive sheet thereof

    CN118006261A